Assessment of the Economic Development of Polish Regions in the Context of the Implementation of the Concept of Sustainable Development - Taxonomic Analysis - Jędrzejczak-Gas, Janina; Barska, Anetta (European Journal of Sustainable Development, 2019)
The aim of the article is to conduct a multidimensional assessment of the diversification of economic development of Polish regions in the context of the progress made in the implementation of the concept of sustainable development in 2010 and 2017. The authors focused primarily on determining the position of Lubusz Province on the economic map of Poland. Given that economic development is a complex category, taxonomic (synthetic) measures developed on the basis of selected methods of multivariate comparative analysis were used in the research. The synthetic measures were constructed using the proposed partial indicators (explanatory variables), which, according to the authors, best illustrate economic development and the idea of sustainable development at regional level. Based on the constructed measures, a linear ordering of Polish regions by level of economic development in the context of the implementation of the concept of sustainable development was made, and the convergence of the orders was examined. In addition, the regions were grouped by level of economic development. Subsequently, the effectiveness of the obtained groupings was evaluated. The research shows that in 2017, compared to 2010, the overall level of economic development in all Polish regions increased. In what concerns Lubusz Province, a conclusion can be made that its position in the overall ranking is improving. Keywords: Linear ordering; Region; Sustainable development; Economic development; Polish regions